Eksistensi Interpolan Deret Ganda Sinusoida - Endang Rusyaman; Hendra Gunawan; Asep Kuswandi Supriatna; Rustam Effendy Siregar (Jurnal Matematika & Sains, 2010)
This paper presents a sufficient condition for the existence of a sinusoidal double series interpolant, that is the function of the form a double Fourier sine series that passes some arbitrary pointsÂ  (xi, yj, cij), with 0 < xi < 1, dan 0 < yj < 1.Â The proof is carried out by decomposing the matrix that contains two variables into the multiplication of two matrices each of which contains one variable only, and showing that both matrices are nonsingular.